The Role of a Notary in the Implementation of Credit Agreements and Settlement of Defaults with a Mortgage Right Guarantee - Rahmatillah, Ananta Mega; Witasari, Aryani; Shallman, Shallman (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze the role of notaries in resolving defaults in credit agreements with collateral rights related to Supreme Court Decision Number 42 PK/TUN/2021. and to analyze the obstacles faced by notaries in resolving defaults in credit agreements with collateral rights related to Supreme Court Decision Number 42 PK/TUN/2021 and their solutions. This study uses a normative juridical research approach. The specifications in this study are descriptive analysis. The theories used include the theory of authority and the theory of legal certainty. Based on the research, it is concluded that the role of notaries who also serve as Land Deed Officials (PPAT) in resolving defaults in credit agreements with collateral rights, as reflected in Supreme Court Decision Number 42 PK/TUN/2021. Notaries not only play a role in making authentic deeds such as sales and purchase deeds and deeds of granting mortgage rights, but also bear preventive legal responsibility to ensure that the collateral object is truly valid both formally and materially. Repressive aspects, Notaries play a role in providing information or becoming expert witnesses in court when the validity of authentic deeds they have made is questioned. Failure by notaries to implement the principle of prudence, such as not verifying land status, physical ownership, or potential disputes, can result in the issuance of legally flawed deeds and lead to the cancellation of mortgage rights and the loss of the bank's preferential rights as a creditor. (2) Internal obstacles include negligence on the part of banks that accept Land Ownership Certificates (SHM) without conducting due diligence, as well as weak integrity and professional ethics from notaries/PPATs who do not verify the validity of the collateral object thoroughly. External obstacles come from the BPN which is negligent in verifying the physical and legal status of the land before issuing SHM, as well as from customers who deliberately hide information about the status of disputes or unclear ownership history of the land used as collateral. Solutions include joint checks on the collateral object by banks, notaries/PPATs, and debtors; strengthening ethical guidance and supervision by professional organizations for notaries/PPATs; strict internal audits at the BPN before issuing certificates; as well as legal education to customers regarding the importance of transparency and validity of guarantee documents.